2020
DOI: 10.5194/essd-12-1789-2020
|View full text |Cite
|
Sign up to set email alerts
|

An integration of gauge, satellite, and reanalysis precipitation datasets for the largest river basin of the Tibetan Plateau

Abstract: Abstract. As the largest river basin of the Tibetan Plateau, the upper Brahmaputra River basin (also called “Yarlung Zangbo” in Chinese) has profound impacts on the water security of local and downstream inhabitants. Precipitation in the basin is mainly controlled by the Indian summer monsoon and westerly and is the key to understanding the water resources available in the basin; however, due to sparse observational data constrained by a harsh environment and complex topography, there remains a lack of reliabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 74 publications
0
30
0
1
Order By: Relevance
“…As the largest (240,000 km 2 ) river basin of the TP, the upper Brahmaputra basin (UBB; also called “Yarlung Zangbo”) has profound impacts on the water security of local and downstream inhabitants (Wang et al., 2020; Yi et al., 2020). The UBB also holds most of the glaciers in the eastern‐Himalaya and Nyainqêntanglha mountains with the strongest mass loss occurring in the monsoon‐affected south‐eastern TP (Yang et al., 2016; Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the largest (240,000 km 2 ) river basin of the TP, the upper Brahmaputra basin (UBB; also called “Yarlung Zangbo”) has profound impacts on the water security of local and downstream inhabitants (Wang et al., 2020; Yi et al., 2020). The UBB also holds most of the glaciers in the eastern‐Himalaya and Nyainqêntanglha mountains with the strongest mass loss occurring in the monsoon‐affected south‐eastern TP (Yang et al., 2016; Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Input precipitation data are updated from Wang et al. (2020) with high spatiotemporal resolution. The calibration and validation steps are completed at Nuxia station and Dexing site of the latest accessible Chinese county Motuo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These gauges provide measurements of precipitation in the liquid phase (i.e., rainfall) at the event timescale. A couple of recent studies have demonstrated the utility of this rain gauge network (Xu et al, 2017;He et al, 2017;Tian et al, 2018;Wang et al, 2020). For instance, Xu et al (2017) evaluated the performance of TRMM and GPM and the dependence on topography and rainfall intensity based on the network.…”
Section: Introductionmentioning
confidence: 99%
“…Their results demonstrated that the data quality of this dense gauge network is strictly controlled, serving as the currently highest gauge density for satellite product evaluation on the TP. Wang et al (2020) used the gauge data to validate their reproduced precipitation dataset. However, there is not a merging product that assimilates the observations from this dense rain gauge network.…”
Section: Introductionmentioning
confidence: 99%